Infliximab tolerance in patients with rheumatoid arthritis in real clinical practice - E. S. Aronova; G. V. Lukina; Ya. A. Sigidin (Научно-практическая ревматология, 2020)
A wide range of biological agents recently introduced into clinical rheumatology determines a special interest in their tolerance. The paper presents the authors’ own data, as well as a review of foreign literature on this issue.Objective: to analyze the tolerability of infliximab (INF) in patients with rheumatoid arthritis (RA) in real clinical practiceSubjects and methods. The analysis included 135 RA patients receiving INF alone or in combination with diseasemodifying antirheumatic drugs.Results and discussion. The total tolerance of INF was satisfactory. Adverse reactions (ARs) were noted in 28.1% of cases, including in 19 (14.1%) patients who had serious ARs that required drug discontinuation.Conclusion. The best tolerance was observed with a combination of INF and methotrexate. The authors draw attention to the need for medical examination prior to each drug administration.